Development of basic motion and gait pattern for multi-legged robot - Nursyamiera Yasmin, Mohd Zawawi (2022)
The multi-legged robot is a biologically inspired robot that resembles an insect or an arthropod organism. This robot is frequently built as a mobile robot for a crewless operation that can outperform a wheeled robot. Furthermore, in its mobility, this robot can maintain both static and dynamic stabilities. The Hexapod-to-Quadruped (Hexaquad) robot, a configurable multilegged robot, is focused and developed in this project with a remote-control configuration and sturdy control unit. The goal of the project is to establish the leg motion and create a sequence. In the control unit design, a 32-bit microcontroller is used as the processing unit on a centralized control unit board. For the real-time and hardware-in-loop methods, the embedded controller is designed fully in Simulink code. In the idle mood, the project's result delivers and develops joint leg control for each Hexaquad leg with precision control, and can stand with a sturdy and reliable foot.